A Systematic Review of Contemporary Challenges and Debates on Chinese Food Security: Integrating Priorities, Trade-Offs, and Policy Pathways - Rong Zeng; Meseret C. Abate; Baozhong Cai; Amsalu K. Addis; Yonas Derebe Dereso (Foods)
Although food security has been a long-standing focus of research and policy in China, significant gaps remain in synthesizing evolving debates across multiple disciplines such as agriculture, economics, environmental science, and politics. This systematic review provides an interdisciplinary analysis of five key areas shaping contemporary discourses on Chinese food security: (1) balancing self-sufficiency with trade dependence; (2) reconciling agricultural intensification with environmental sustainability; (3) addressing urbanization’s impact on small-scale agriculture transformation; (4) enhancing resilience to climate change through targeted investments and policies; and (5) improving food safety standards to meet growing consumer concerns. This review harnesses insights from global academic databases—including Web of Science, Scopus, and Google Scholar—to map interdisciplinary debates on Chinese food security, synthesizing peer-reviewed studies and policy reports from 2010 to 2024. Drawing upon empirical evidence from recent studies, this review highlights critical tensions, such as those between economic growth priorities and ecological preservation, and explores pathways for sustainable development within China’s unique socio-political context. The findings underscore that robust food security strategies must integrate diverse perspectives while adapting to emerging challenges such as climate change impacts and shifting consumer demands. To ensure sustainable outcomes, future policies should prioritize inclusivity by incorporating insights from ongoing research agendas across disciplines. This review can be used as a benchmark for the advancement of research agendas focused on developing sustainable solutions to the complex challenges of food security in China and beyond.